Case Report: Microangiopathic Hemolytic Anemia With Normal ADAMTS13 Activity - Osti, Nicola; Beschin, Greta; Goldin, Marzia; Guidolin, Lucia; Panero, Enrico; Sartori, Alice; Parisi, Alice; Cantini, Maurizio; Pizzolo, Francesca; Olivieri, Oliviero; Friso, Simonetta (Frontiers in Medicine, 2021)
Thrombotic microangiopathies (TMAs) include a heterogeneous group of diseases characterized by abnormalities in the vessel walls of arterioles and capillaries resulting in microvascular thrombosis that typically presents with a microangiopathic hemolytic anemia (MAHA) and severe thrombocytopenia. We describe here the case of an 82-years-old woman, who came to our attention for a clinical condition consistent with thrombotic microangiopathy. Even if initially highly suggestive for a thrombotic thrombocytopenic purpura (TTP), the elevated ADAMTS13 activity together with the alteration of the main coagulation parameters (D-dimer elevation, fibrinogen consumption, slightly prolonged prothrombin time), induced us to consider several other diseases in the differential diagnostic process. The case evolved toward a suspected overlapped secondary hemophagocytic syndrome, though the hyperferritinemia was finally interpreted within the frame of a cytokine storm. After a complex diagnostic work-up, the clinical and biochemical parameters guided us toward the diagnosis of a cancer-related microangiopathic hemolytic anemia (CR-MAHA) secondary to a relapsing breast cancer with multiple metastatic localizations. Prednisone 1 mg/kg body weight was started, and several units of fresh frozen plasma were infused, obtaining a good control of the hemolysis. No specific oncological therapies were, however, possible, due to the older age and the critically compromised general condition of the patient, therefore, after clinical stabilization, the patient was discharged for treatment in a palliative care Hospital.